Overexpression of MicroRNA-106b-5p Attenuates Kidney Injuries after Deep Hypothermic Circulatory Arrest in Rats - Yu, Lei; Gu, Tianxiang; Liu, Yu; Jiang, Xuan; Shi, Enyi (The Thoracic and Cardiovascular Surgeon, 2018)
Background MicroRNAs (miRNA) have been identified to exert a wide range of biological functions in acute kidney injury (AKI) after deep hypothermic circulatory arrest (DHCA). We sought to investigate the renoprotection of miRNA-106b-5p in a rat model of DHCA by targeting phosphatase and tensin homolog (PTEN).Methods Overexpression of miRNA-106b-5p in vivo was conducted by directly injection of lentivirus vectors containing pre-miRNA-106b-5p into the renal parenchyma of the animals under the ultrasound guidance 7 days before DHCA. The vehicle or control lentivirus vectors were given to the control group or the control vector group, respectively. Renal function and apoptosis activity were evaluated by serum cystatin C, serum/tissue neutrophil gelatinase-associated lipocalin (NGAL), and terminal deoxynucleotidyl transferase dUTP nick-end labeling assay (TUNEL) at 24 hours after surgery. Expressions of miRNA-106b-5p, PTEN, and caspase-3 in the kidney were evaluated by quantitative real-time polymerase chain reaction and western blot analysis.Results Transfection of pre-miRNA-106b-5p significantly enhanced the expression of miRNA-106b-5p and dramatically downregulated the expressions of PTEN in the kidney compared with the control group. Renal functions were markedly protected by pretreatment with pre-miRNA-106b-5p as evidenced by decreases in serum cystatin C and serum/tissue neutrophil gelatinase-associated lipocalin at 24 hours after surgery. The pre-miRNA-106b-5p group showed significantly fewer apoptotic cells and lower levels of caspase-3 activation than the control group.Conclusions Overexpression of miRNA-106b-5p attenuates kidney injuries after DHCA, possibly by inhibition of PTEN.
Keywords: deep hypothermic circulatory arrest; phosphatase and tensin homolog; microRNAs